Analisis Faktor-Faktor yang Memengaruhi Minat Berperilaku dalam Penggunaan Sistem Informasi Akuntansi pada Kinerja Karyawan - Trisnayanti, Ni Komang Indira; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 32 No 5 (2022), 2022)
Measuring the success of information systems can be done using the Delone & McLean information system success model, but to measure technology acceptance can be done using the Technology Acceptance Model (TAM). The purpose of this study is to analyze the factors that influence behavioral interest in the use of Accounting Information Systems on employee performance. This research was conducted at BPR in Denpasar City, with the number of respondents 84 users of the Accounting Information System (AIS). Data collection using questionnaires and data analysis techniques used multiple linear regression with SmartPLS 3.0 tool. Based on the results of the analysis, it was found that perceived usefulness and perceived ease of use had a positive effect on behavioral interest in using AIS. Perceived usefulness and behavioral interest in using AIS have a positive effect on the performance of BPR employees in Denpasar City.                 Keywords: Behavioral Interests; Accounting Information System; Employee Performance; Perceived Usefulness; Perceived Ease of Use.